2021
DOI: 10.1021/acssynbio.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Gas-Fermenting Clostridium ljungdahlii for Efficient Co-production of Isopropanol, 3-Hydroxybutyrate, and Ethanol

Abstract: Rational design and modification of autotrophic bacteria to efficiently produce high-value chemicals and biofuels are crucial for establishing a sustainable and economically viable process for one-carbon (C1) source utilization, which, however, remains a challenge in metabolic engineering. In this study, autotrophic Clostridium ljungdahlii was metabolically engineered to efficiently co-produce three important bulk chemicals, isopropanol, 3-hydroxybutyrate (3-HB), and ethanol (together, IHE), using syngas (CO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Their research may provide a safer new idea for the production of benzoic acid as a preservative. Some researchers engineered Clostridium ljungdahlii to produce isopropanol, 3-hydroxybutyric acid, ethanol and other substances [ 61 ], which research provides conditions for the use of single-carbon source materials to produce a large number of chemicals. There are also some studies providing a platform for the production of some industrial substances such as L-citrulline, flavan-3-ols, β-carotene, etc.…”
Section: Research and Application Of Engineered Probioticsmentioning
confidence: 99%
“…Their research may provide a safer new idea for the production of benzoic acid as a preservative. Some researchers engineered Clostridium ljungdahlii to produce isopropanol, 3-hydroxybutyric acid, ethanol and other substances [ 61 ], which research provides conditions for the use of single-carbon source materials to produce a large number of chemicals. There are also some studies providing a platform for the production of some industrial substances such as L-citrulline, flavan-3-ols, β-carotene, etc.…”
Section: Research and Application Of Engineered Probioticsmentioning
confidence: 99%
“…was published, describing the production of up to 13.4 g L –1 by a recombinant C. ljungdahlii . [ 50 ] Considering these results, it can be concluded that A. woodii might have an alternative acetone‐isopropanol conversion pathway in its metabolism and it could be a better isopropanol producer. Unfortunately, the respective gene could not yet be identified.…”
Section: Discussionmentioning
confidence: 99%
“…The development of genetic tools and synthetic biology approaches has opened up possibilities for the metabolic engineering of several acetogens ( Köpke et al, 2010 ; Shin et al, 2019 ; Zhao et al, 2019 ; Jin et al, 2020 ). Using such tools, the heterologous expression of biosynthetic pathways for producing desired chemicals has expanded the product spectrum of acetogens, including isoprene, isopropanol, acetone, and 3-hydroxybutyrate (3-HB; Jones et al, 2016 ; Diner et al, 2018 ; Woolston et al, 2018 ; Karim et al, 2020 ; Jia et al, 2021 ). Although they were proof-of-concept production, as their titers were considerably low due to concurrent production of native metabolites as byproducts, significant improvements can be achieved with strain engineering that redirects carbon fluxes toward desired chemicals.…”
Section: Biotechnological Applications Of Acetogensmentioning
confidence: 99%
“…The positive effect of this strategy was confirmed by the overexpression of native AOR in C. carboxidivorans, which resulted in higher ethanol production ( Cheng et al, 2019 ). Recently, a novel acetate reassimilation pathway containing two acyl-CoA synthetases (ACS from C. ljungdahlii and FadKM1/2 from E. coli ) that catalyze acetate conversion to form acetyl-CoA was tested in C. ljungdahlii along with overexpression of native AOR enzymes ( Jia et al, 2021 ). Introduction of the pathway into an engineered strain to produce isopropanol successfully reinforced acetate assimilation, achieving significantly reduced acetate formation and increased production of ethanol and isopropanol through syngas fermentation.…”
Section: Biotechnological Applications Of Acetogensmentioning
confidence: 99%